Implementation of Character Education through Active Learning for Islamic Religious Education Teachers - Zahra Rahmatika; Asfahani Asfahani; Gusma Afriani; Mohammad Saro’i; Muhammadong Muhammadong (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2024)
The purpose of this study was to investigate how active learning strategies can enhance student engagement and facilitate the internalization of Islamic values. This study used a qualitative approach, data were collected through semi-structured interviews, classroom observations, and document analysis involving IRE teachers. The study findings revealed that active learning significantly increased student participation and moral reflection, offering a more dynamic and practical approach to character education. Teachers reported that activities such as role-playing, group discussions, and problem-solving not only made religious teachings more relevant but also encouraged students to apply Islamic principles in real-life situations. However, the study also identified challenges, including lack of training and resources, and the need to contextualize active learning within an Islamic framework. This study contributes to the broader discourse on educational strategies that nurture intellectual and moral development, offering insights and recommendations for improving character education in Islamic educational settings. Future research should focus on the long-term impact of these strategies and the development of specific training programs for IRE teachers.